Structure, Electrical, and Optical Properties of (Na1/2Bi1/2)TiO3–1.5at.%Bi(Zn1/2Ti1/2)O3 Lead‐free Single Crystal Grown by a TSSG Technique. Issue 6 (19th February 2014) - Chen, Chao; Zhang, Haiwu; Zhao, Xiangyong; Deng, Hao; Li, Long; Ren, Bo; Lin, Di; Li, Xiaobing; Luo, Haosu; Chen, Zhen; Su, Jun; Damjanovic, D.
<x xml:space="preserve">Abstract</x> Lead‐free single crystal (Na1/2Bi1/2)TiO3–1.5 at.%Bi(Zn1/2Ti1/2)O3 (NBT–1.5BZT) with dimension of Φ35 mm × 12 mm was successfully grown by a top‐seeded solution growth technique. The average and local structure were studied by a combination of X‐ray diffraction and Raman spectroscopy. The electric and optical properties of <001>‐oriented single crystals were investigated systematically. Compared with pure NBT, the piezoelectric constant and transmission coefficient were both enhanced, that is, from 62 pC/N and ~60% to 121 pC/N and ~70%, respectively. Furthermore, domain structure observation suggested that the <110>‐oriented tetragonal ferroelastic domains in NBT were suppressed at room temperature with addition of BZT, which was responsible for the improved piezoelectric and optical properties of NBT–1.5BZT single crystal.